A IMPORTÂNCIA DAS RELAÇÕES AFETIVAS NO PROCESSO DE ENSINO E APRENDIZAGEM: UMA PERSPECTIVA INCLUSIVA - Ana Mayra Samuel Silva; José Eduardo de Oliveira Evangelista Lanuti; Ana Virginia Isiano Lima; Danielle Aparecida do Nascimento Santos; Janiele de Souza Santos; Denner Dias Barros; Elisa Tomoe Moriya Schlünzen (Colloquium Humanarum, 2015)
The affection, set of psychic phenomena that manifest themselves in the form of emotions and feelings can be fundamental in the processes of teaching and learning. Emotion and intellect are inseparable dimensions of the human being and this inseparability must be considered in the planning and development of educational activities. Thus, throughout this article will be exposed to the importance of personal relationships in educational attendances at the Target Audience Students attending the Special Education Promotion Centre for Digital Inclusion, Social and School (CPIDES), Faculty of Sciences and Technology (FCT / UNESP). Through a literature review and based on the results of the consultations held between semesters of 2013 and 2014 it was concluded that the importance given to personal relationships during the sessions contributed to student learning, considering the way began to relate and understand the content covered.